ECONOMIC GROWTH EFFECT ON ENVIRONMENTAL POLLUTION IN INDONESIA - Normanda Eka Shakti; Prayudi Setiawan Prabowo (Publikasi Inspirasi Indonesia, 2026)
This study examines the impact of economic growth on environmental pollution across Indonesia's provinces, utilizing Gross Regional Domestic Product (GRDP) at current market prices as the primary economic indicator and population density as a control variable. Employing a quantitative approach with cross-sectional secondary data from Indonesia's Central Statistics Agency (BPS), the research conducts multivariate regression analysis on data from all 34 provinces. Comprehensive diagnostic tests, including assessments of normality, multicollinearity, autocorrelation, and model specification, were performed to validate the statistical model. The findings reveal that both GRDP and population density exert statistically significant positive effects on environmental pollution, though the magnitude of these effects is relatively modest. The model explains approximately 44.35% of the variation in environmental pollution, suggesting that additional factors beyond economic and demographic variables contribute substantially to pollution dynamics. This research provides contemporary empirical support for the Environmental Kuznets Curve (EKC) hypothesis in the Indonesian context, emphasizing the necessity for integrated policy approaches that balance economic development with environmental sustainability.